OPTIMALISASI PARTISIPASI ORANG TUA MELALUI KEGIATAN PARENTING DI DESA LAU GUMBA KECAMATAN BERASTAGI KABUPATEN KARO - Parapat, Asmidar; Nofianti, Rita; Latifa, Siti (Seminar Nasional Sosial Sains dan Teknologi Halal, 2022)
This study discusses optimizing parental participation in parenting programs. This research is motivated by precise findings that reveal that the current parenting program has not been running according to its normal goals. This is evidenced by the absence of parental interest in participating in parenting programs held at educational institutions. The reason is the result of busy work, individual problems that cannot be left behind, etc. Therefore, this research is directed to describe and describe how the efforts of the city of Lau Gumba in achieving increased parental cooperation in the parenting program. The purpose of this study is to collect information and data regarding: (1) the techniques used by the program coordinator to increase parental support in the parenting program, (2) the types of programs carried out by the program coordinator to increase parental cooperation in the parenting program, (3) the results obtained by increasing parental interest in parenting programs. Theories or concepts used in this study include the theory of importance and the theory of participation. This research was conducted in Lau Gumba Village, Berastagi District, Karo Regency, through three stages, namely preparation, implementation, and details of examination results. This study uses an interesting technique with a descriptive method with a qualitative approach. The test subjects used as a source of information were six people, PAUD Kober supervisors and 5 guardians. Information collection strategies used are observation and interviews. The final point is that in coordinating important programs that can promote parental cooperation, it is important to focus on the methodologies and techniques used, and the results obtained by both the organization and the parents. Keywords: Parental Participation, Parenting Program